1996
DOI: 10.1177/026361749601300609
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phenol from Aqueous Solution by Adsorption on to Coal Fly Ash

Abstract: The present work examines the possible use of fly ash, a byproduct of coal power stations, as a means of removing phenol from water, or equivalently, of restricting its movement in solid wastes or soil. Equilibrium experiments were performed to evaluate the removal efficiency of fly ash. The adsorption experiments were undertaken using fly ash treated at three different pH levels and with three different temperatures. The results indicate that although phenol can be removed from water, this depends markedly on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The adsorption experiments were undertaken using fly ash treated at three different pH levels and with three different temperatures. The results indicated that although phenol can be removed from water, this depends markedly on the temperature and pH value of the treatment solution employed [141]. Adsorption isotherms for adsorption of phenol, 3-chlorophenol, and 2,4-dichlorophenol from water onto fly ash were determined [142].…”
Section: 33mentioning
confidence: 99%
“…The adsorption experiments were undertaken using fly ash treated at three different pH levels and with three different temperatures. The results indicated that although phenol can be removed from water, this depends markedly on the temperature and pH value of the treatment solution employed [141]. Adsorption isotherms for adsorption of phenol, 3-chlorophenol, and 2,4-dichlorophenol from water onto fly ash were determined [142].…”
Section: 33mentioning
confidence: 99%
“…The adsorption experiments were undertaken using fly ash treated at three different pH levels and with three different temperatures. The results indicated that although phenol can be removed from water, this depends markedly on the temperature and pH value of the treatment solution employed [116].…”
Section: Removal Of Organic Compounds From Watermentioning
confidence: 99%
“…Its properties make it difficult to biodegrade ofloxacin or remove ofloxacin from aqueous solution. Among the techniques for removal of ofloxacin from wastewater, adsorption has been proved to be an effective and attractive process because of its inexpensive nature and ease of operation [2][3][4][5][6]. However, only a limited amount of the adsorption behaviors of ofloxacin have been reported [7].…”
Section: Introductionmentioning
confidence: 99%